SAR Altimetry Data as a New Source for Swell Monitoring. Issue 7 (29th March 2022) - Altiparmaki, Ourania; Kleinherenbrink, Marcel; Naeije, Marc; Slobbe, Cornelis; Visser, Pieter
Abstract: This article shows the first spectral analysis of fully‐focused Synthetic Aperture Radar (FFSAR) altimetry data with the objective of studying backscatter modulations caused by swells. Swell waves distort the backscatter in altimetry radargrams by means of velocity and range bunching. These swell signatures are visible in the tail of the waveform. By locally normalizing the backscatter and projecting the waveforms on an along‐/cross‐track grid, satellite altimetry can be exploited to retrieve swell information. The analysis of FFSAR spectra is supported by buoy‐derived swell‐wave spectra of the National Oceanic and Atmospheric Administration network. Using cases with varying wave characteristics, we discuss the altimetry‐derived spectra and relate them to what is known from side‐looking SAR imaging systems. Besides having a vast amount of additional data for swell‐wave analysis, altimeter data can also help us to better understand the side‐looking SAR spectra. Plain Language Summary: Swells are long‐crest waves induced by storms. They can travel thousands of kilometers and impact remote shorelines. They also interact with local wind generated waves and currents. It has been shown that the presence of swell lowers the quality of the geophysical parameters which can be retrieved from the delay/Doppler radar altimeter data. This, in turn, affects the estimation of small‐scale ocean dynamics. In addition, the resolution offered by the delay/Doppler processing schemes, which is approximately 300 m in the along‐track direction, does not allow to resolve swells. This work presents a method which demonstrates that Synthetic Aperture Radar (SAR) altimeters show potential to retrieve swell‐wave spectra from fully‐focused SAR altimetry processed data for the first time, and proposes thus, that SAR altimetry can serve as a source for swell monitoring. Key Points: Synthetic Aperture Radar (SAR) altimetry data have potential for retrieval of swell spectra We suggest a processing approach to derive altimetry SAR spectra comparable to side‐looking SAR The main intensity modulation mechanisms are velocity bunching and range bunching